Information security : 17th International Conference, ISSA 2018, Pretoria, South Africa, August 15-16, 2018, Revised selected papers /: 17th International Conference, ISSA 2018, Pretoria, South Africa, August 15-16, 2018, Revised selected papers. (2019) - Unknown
No abstract available